From Impulse to Action—Noah (2014) and Exodus: Gods and Kings (2014) as Secular Bible Epics - Sylvie Magerstädt (Religions, 2021)
Several large-scale Bible epics have been produced in the decade after the revival of epic cinema at the turn of the millennium. Yet, while many biblical films of this period were primarily aimed at religious audiences, Darren Aronofsky’s Noah (2014) and Ridley Scott’s Exodus:Gods and Kings (2014) stand out due to their broader epic appeal and religious skepticism. Using Gilles Deleuze’s concepts of the impulse-image and the action-image as framework, this article analyses some of the nuances and complexities of both films. It argues that although both films offer scale and spectacle consistent with older biblical epics, the portrayal of their lead characters as a man determined on destruction (Noah) and religious skeptic and warrior (Exodus) differentiates them from traditional biblical cinema. Additionally, comparing both films helps articulate nuances within Deleuze’s movement-image that are often overlooked. Having proclaimed that modern cinema brings with it a crisis of truth that challenges the certainties of classic American cinema and its clear ideas on morality and belief, Deleuze ultimately calls for a leap of faith to reinstate the possibility of action. The article concludes that Noah and Exodus offer us a bit of both—spiritual uncertainty and a return of classic epic cinema.